Clinical and Morphological Features of Respiratory Disorders in Preterm Neonates - A. M Golubev (Obŝaâ Reanimatologiâ, 2008)
Objective: to determine the causes of preterm labor and the factors contributing to the development of acute respiratory distress syndrome (ARDS) in the newborn. Subjects and methods. The paper presents the results of analyzing case histories and autopsy protocols of preterm neonates who died from ARDS. The study group comprised 20 (36.6%) very low-weight neonatal infants. Twelve (21.8%) neonates out of all the infants received the exogenous surfactants Curosurf and Surfactant BL. Lungs and placentas were histologically studied. Results. The study has demonstrated that various placen-tal abnormalities are one of the risk factors of preterm labor and ARDS. Intranatal amniotic fluid aspiration is a poor predictor. Conclusion. The efficiency of therapy with the exogenous surfactants depends on the quality of care delivered to a baby at birth, the time of switching the patient to artificial ventilation and the time of administration of a surfactant. Exogenous surfactants should be administered only in obstetric facilities that have all conveniences at their disposal to render a specialized aid to preterm infants. Key words: preterm neonate infants, acute respiratory distress syndrome, exogenous surfactants, primary atelectases, hyaline membranes.